PENERAPAN PEMBELAJARAN MATEMATIKA REALISTIK DAN PEMBELAJARAN SAINTIFIK DALAM MENINGKATAN KEMAMPUAN BERPIKIR KRITIS - Gita Dwi Fitriyani (Integral : Pendidikan Matematika, 2017)
Some life skill mathematics, which are needed by the students in this 21 stcentury in order to support their life, are creativity and innovation, critical thinking andproblem solving, communication, and collaboration. Critical thinking skill is needed inthis modern era, yet some studies show that seventh grade student’s critical and creativethinking skills are not satisfying yet. The research objectives to be achieved describe thedifference increase of critical thinking skill between student who got realisticmathematics education and scientific approach. The research method was quasiexperimental research with pretest-posttest two treatment designs. The population of thisresearch was the seventh grade students in one of junior high school in West Bandung.The samples of this research are two classes that choosen based on mathematicsteacher’s advice. Research instruments include tests of critical thinking skill andobservation. The result showed there was difference increase of critical thinking skillbetween student who got realistic mathematics education and scientific approach,students who got realistic mathematics education has better increase of critical thinkingskill than students who got scientific approach.Key word: critical thinking skills, realistic mathematics education, scientific approach.